A ilusão da redução das assimetrias regionais a partir das alterações da rede rodoviária em Portugal - Pacheco, Elsa (2016)
Road accessibility influences the development of territories. However, the apparent certainty about its positive impact on development has been questioned, weakening the intervention for the desirable sustainability of land development. Our work is underpinned by studies on road accessibility in the last two decades in Portugal, based on successive National Road Plans, to show the existing contradiction between the principles of decreasing regional inequalities defined therein and the territorial effects triggered, either through biased expectations of the population, or through the ensuing territorial dynamics.